Savage! : The Robbie Savage Autobiography - Savage, Robbie and Self, Janine (Edinburgh Mainstream Publishing, 2010)
Robbie Savage could have been just another Manchester United reject. Instead, he used the Old Trafford scrapheap as a springboard to become one of the most instantly recognisable footballers in the Premier League. This title provides an insight into the extraordinary life of this sportsman.
Include Illustration
Keywords: Soccer players -- Wales -- England